Chemistry of wheat gluten proteins: Qualitative composition. Issue 1 (15th June 2022) - Wieser, Herbert; Koehler, Peter; Scherf, Katharina A.
Abstract: Background and Objectives: Wheat gluten proteins make up one of the most complex protein aggregates in nature. Their qualitative and quantitative composition is determined by genetic and environmental factors as well as technological processes. Findings: Gluten proteins comprise ω5‐, ω1, 2‐, α‐, and γ‐gliadins as well as high‐molecular‐weight glutenin subunits (HMW‐GS) and low‐molecular‐weight (LMW) GS. About 50% of gluten proteins are monomeric gliadins with MWs from 28, 000 to 55, 000, while about 15% are present as disulfide‐linked oligomeric proteins with MWs between 70, 000 and 700, 000, called HMW‐gliadins. The remaining 35% are disulfide‐linked polymeric glutenins with MWs from 700, 000 to more than 10 million. Intrachain disulfide bonds, present in all types except ω‐gliadins, stabilize the three‐dimensional structure, while interchain disulfide bonds, mainly linking HMW‐GS and LMW‐GS, generate oligomers and polymers. Conclusions: In this review, we provide an updated and detailed insight into the chemistry of wheat gluten proteins with a focus on the qualitative composition. Significance and Novelty: An enhanced understanding of gluten protein structure and how it is affected will be essential to select and breed more resilient wheat varieties with favorable processing properties to help ensure nutrition and food security worldwide.